COMPOSIÇÃO QUÍMICA, PROPRIEDADES TÉRMICAS E OXIDATIVAS DO ÓLEO VEGETAL OBTIDO DE Elaeocarpus serratus (AZEITONA DO CEILÃO) - DE SANTANA, Brenda Rafaela Berto; DOS SANTOS, Maiara Viviane Oliveira; COUTINHO, Eduardo João; SANTIAGO, Etenaldo Felipe; SIMIONATTO, Euclesio (ANAIS DO ENIC, 2024)
-